Degenerative and regenerative changes in murine skeletal muscle after injection of venom from the snake Bothrops asper: a histochemical and immunocytochemical study. - Arce, Vilma (1991)
The degenerative and regenerative changes in murine skeletal muscle after injection of Bothrops asper venom were studied by histological, lectin histochemical and immunocytochemical techniques. According to our observations, the process was divided into four main stages: (a) During the first 3 days prominent degenerative events took place in skeletal muscle fibres, capillaries, arteries, veins and intramuscular nerves. An inflammatory infiltrate was abundant after the first day and removal of necrotic material was well advanced by the third day. (b) Muscle regeneration was evident by the fourth day. From 4 to 6 days there were two populations of regenerating muscle fibres, one of apparently normal fibres located in areas where capillary vessels were abundant, and another population of groups of regenerative fibres showing signs of degeneration. This second type of fibre was predominant in areas where the number of capillaries was greatly reduced. (c) One and 2 weeks after envenomation areas of small regenerative fibres of normal morphology and areas of degenerating regenerative fibres were observed. The latter were abundant in regions of dense fibrotic tissue and scarce capillaries. (d) Finally, at 4 and 8 weeks after envenomation there were both areas of fibrosis and areas where regenerating muscle fibres predominated. However, the diameter of these fibres was abnormally small, an indication that they may have been atrophic fibres. It is suggested that muscle regeneration is partially impaired after myonecrosis induced by Bothrops asper venom, probably due to the damage induced by this venom on muscle microvasculature and nerves.